Integral Transportation Systems in Military Transport Aircraft Supply - Kovačević, Dražen; Blašković, Jasna; Maković, Branko (Promet - Traffic&Transportation, 2012)
Supply of goods, equipment and soldiers by militwy transportaircraft can serve as a support to airborne landing operation,support to encircled forces, and support to forces leadinga gue1rilla war. Transport aircraft are designed in such a wayas to be able to cany containers, pallets, most of land vehiclesand helicopters. Militwy transport aircraft can be grouped intothose that were originally designed for military transp01t andthose that are modified civilian aircraft and helicopters. Supplypallets can be wooden, metal, can be airdropped in 'taxiing','low-flight', and can also be fitted with a parachute or'retrorocket' for reducing the ground impact. Pallets canamong other things carry liquids, heavy combat and ca1rier vehicles,artillery and rocket weapons and valious containers.Pallets are usually pe1manently deformed at ground impact.Nowadays, high precision of airdrop has been achieved. Containersare used to carry various equipment, food, fue~ weapons,ammunition etc. It is to be expected that the containers,wmoured combat and other vehicles will be redesigned so asto provide more efficient transport and fast a!Tangement ofhigh-mobility units, whereas the form of the future militarytransport aircraft will not undergo substantial changes. By adjustingand standardising the transporlation vehicles, integraltransportation means and cwgo, the overall combat efficiencywill be increased, the a~rangement time especially shortenedand the air supply safety increased.